Enzyme‐Mediated Intracellular Polymerization of AIEgens for Light‐Up Tumor Localization and Theranostics. Issue 5 (16th December 2021) - Qi, Guobin; Liu, Xingang; Shi, Leilei; Wu, Min; Liu, Jingjing; Liu, Bin
Abstract: Improving the enrichment of drugs or theranostic agents within tumors is vital to achieve effective cancer diagnosis and therapy with reduced dosage and damage to normal tissues. In this work, an enzyme‐mediated aggregation‐induced emission fluorogen (AIEgen) intracellular polymerization strategy that can simultaneously promote the accumulation and retention of the AIEgen in the tumor for prolonged imaging and enhanced tumor growth inhibition is described. An AIEgen‐peptide conjugate (D2P1) and cyanobenzothiazole‐cysteine (3CBT) that can undergo rapid condensation reaction to form nanoaggregates in tumor cells are rationally designed. Upon tumor‐specific cathepsin protease reaction, the cleavage of peptides induces condensate polymerization between the exposed cysteine and 2‐cyanobenzothiazole on 3CBT, triggering accumulation of D2P1 into the tumor site, leading to fluorescence light‐up. Such enzyme‐mediated polymerization of D2P1 and 3CBT alters cellular motility via disrupting actin organization and in turn inhibiting cell proliferation. In addition, due to the built‐in intrinsic photosensitization property of the AIEgen, the accumulation of D2P1 can remarkably promote the tumor photodynamic therapy effect in vivo under light irradiation. This study thus represents the enzyme‐mediated intracellular polymerization system with high potential to improve the diagnostic and therapeutic outcomes of tumors in vivo. Abstract : An aggregation‐induced emission fluorogen‐peptide conjugates (D2P1) and 3CBT that can undergo in situ polymerization to form aggregates in tumor cells are rationally designed. Upon tumor‐specific cathepsin B enzyme reactions, the peptide cleavage on D2P1 induces covalent polymerization between 3CBT, which triggers aggregation and accumulation of D2P1 into the tumor site, resulting in enhanced fluorescence signal and tumor treatment efficacy.